The influence of regional revenue and expenditure budget realization report and financial report information on APBD determination: Study of regional government in Indonesia - Pamungkas, Bambang; Sutarti, Sutarti (International Journal of Emerging Trends in Social Sciences, 2025)
This study aimed to empirically investigate the influence of Regional Revenue and Expenditure Budget (APBD) realization as well as regional financial report information on APBD determination (PAPBD). Quantitative data were obtained from regional government financial report spanning from 2017 to 2020. Furthermore, the population comprised regional government in Indonesia, with a sample of 538 city and district governments as well as 2,126 observations selected through purposive sampling. Panel data analysis was conducted using GLS-RE method to estimate parameters of the direct influence model. The results showed that APBD realization report had a positive effect on APBD determination, while financial report information had a negative effect. This had significant implications for regulations and local government, specifically in developing countries such as Indonesia. Moreover, the results showed the importance of budget realization report (LRA) in informing APBD decisions and the necessity of timely financial information to ensure appropriate budget allocation.